The medical dilemmas posed by coronavirus ICU bed shortage from a biojuridical perspective - Bejar Chuchon, Eva Margiory (2021)
This article will analyze the medical dilemmas brought about by COVID-19, a pandemic that revealed the shortcomings of each country in the field of health. As we know, the rapid growth in the number of infected persons alarmed the States due to the scarcity of beds in intensive care units. For this reason, we will carry out an exhaustive analysis, from a national and international approach, of the procedures to be able to access an ICU bed. Also on the different criteria that have been established within the health centers to grant such beds. Thus, in the conclusions, we will be able to establish the best possible criteria. Let us remember that we are talking about human lives, which need and deserve an analysis that goes beyond our legal system.